American Quarantine: The Right to Housing in a Pandemic. Issue 2 (1st December 2020) - Honig, Bonnie
Abstract: In the US, quarantine requires we stay home, but many do not have homes to stay in or may lose theirs due to job or wage loss. For this reason, moratoria have been put on evictions. At the same time, after the latest police killings, and during ensuing protests against racist policing in June 2020, some were arrested for curfew violations, many pulled off the streets but others out of their homes or off their stoops. A real right to housing addresses both homelessness and uncurbed police powers that round up and break in. To address current emergencies and correct larger wrongs of American life, a rent jubilee would better protect tenants than a moratorium. It could be construed as a "taking, " allowed by the 5th Amendment, compensating landlords for their properties' being taken to serve a "public use." Popular takings, too, are rising up on behalf of a right to housing that goes beyond rent moratoria for some and the provision of low-grade "public housing" for others.